ANALISIS SEMIOTIKA TIPOGRAFI: EKSISTENSI HELVETICA DALAM KARYA DESAIN - Dede Kurniawan (UNIVERSITAS NUSA PUTRA, 2022)
This study attempts to explore the existence of the Helvetica font in several design works by borrowing the typographical semiotic perspective offered by Theo van Leeuwen. This study applies qualitative research methods by collecting data from observations, interviews and documentation. The results show that the Helvetica font still exists in design works because of its neutral, neutral character in the sense of not taking sides in any of its meanings, for example only thin which can be interpreted as exclusive, luxurious or black which is interpreted as bold, arrogant. because Helvetica weights ultra light to extra black. Then the expansion is created and compressed (strongly narrowed), compressed (narrowed), and extended (expanded). This feature is commonly used for space requirements in a design work. The slope feature indicates that the Helvetica font has a regular type (upright), italic (italics). and curvature where Helvetica has a rounded version that allows Helvetica to be used for the needs of friendly, soft, and natural types of designs. The features in the Helvetica typeface can answer the design needs of any type, a typeface with neutral, readability and legibility characteristics that only present clear information and without exaggerated ornaments such as Decorative typefaces. This then allowed Helvetica to be included in several design works and made Helvetica itself still exist today.